A review on diagnostic assessments of tracheal stenosis - Mojdeh Monjezi; Milad Rismanian; Hamidreza Jamaati (BioMedical Engineering OnLine)
Abstract Tracheal stenosis (TS) is a pathological condition characterized by a reduction in the trachea diameter. It is a common complication after prolonged endotracheal intubation but may also arise from autoimmune or inflammatory processes. Clinicians can select the most appropriate treatment option based on individual patient conditions. Therefore, precise localization and evaluation of the stenosis are essential to ensure safe and effective treatment. This review summarizes current research on TS diagnosis and assessment, encompassing functional, imaging, and bronchoscopy methods. The characteristics, advantages, and disadvantages of each technique are discussed in relation to their application in the diagnosis and assessment of TS. Bronchoscopy is considered the cornerstone of TS diagnosis, and novel adjunct imaging modalities have emerged to enhance its accuracy. We explore advanced endomicroscopic methods, such as endobronchial ultrasound (EBUS), photoacoustic endoscopy (PAE), optical coherence tomography (OCT), and confocal laser endomicroscopy (CLE). Among these, EBUS is clinically approved for diagnosing lesions with high resolution and acceptable penetration depth. OCT and CLE offer real-time imaging for peripheral lesions and potentially malignant nodules, but their use is limited by cost and availability in low-resource settings. Therefore, bronchoscopy, with biopsy techniques as needed, remains the optimal approach for diagnosing tracheal stenosis.